A 3D numerical simulation of a mixed convection flow in a building integrated photovoltaic thermal (BIPV/T) front - Boufkri Malika (EDP Sciences, 2021)
In the present paper, a numerical study of mixed convection flow of a three-dimensional building integrated photovoltaic thermal front (BIPV/T) has been investigated. The configuration consists of a cubical system heated by a solar panel partition. The left wall has an inlet damper at the bottom allowing the cold air flotation in a gap between the solar panel and the opposite vertical insulated wall. The finite volume method is used to analyze the dynamic, thermal fields and the heat transfer flow of the system. The results revealed that the heat transfer rate is affected by Reynolds and Nusselt number’s variations.